Sociolinguistic Variations in the Novel Ronggeng Dukuh Paruk by Ahmad Tohar - Nur Ameliya Hasan; Ellyana Hinta; Muslimin; Sayama Malabar (Raja Zulkarnain Education Foundation, 2026)
This study aims to describe the sociolinguistic variation in the novel Ronggeng Dukuh Paruk by Ahmad Tohari based on age and gender, and explain its relevance in learning Indonesian language and literature. Research was conducted on the novel Ronggeng Dukuh Paruk by Ahmad Tohari as a source of research data. The research population was in the form of all the speeches of the characters in the novel Ronggeng Dukuh Paruk, while the research sample was in the form of the speech of the characters that contained sociolectic variations. The research instrument uses the researcher as the main instrument with the help of a data card. Data collection is carried out through reading techniques, tagging techniques, and recording techniques. The collected data was analyzed using a qualitative descriptive method through the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that in the novel Ronggeng Dukuh Paruk there are various forms of sociolinguistic variation that reflect the social conditions of the people of Dukuh Paruk. This variation is seen through the use of local vocabulary, traditional expressions, and forms of speech that show the social identity of the speaker. Based on age, it was found that there was a difference in language use between older characters and younger characters. Older characters tend to use speech that is loaded with the values of local traditions and culture, while younger characters use simpler and more direct language. Based on the type of gender, there are differences in word choice and speaking styles between male and female figures that reflect their respective social roles in society. This research has relevance in learning Indonesian language, especially in novel analysis materials and sociolinguistic studies. The research findings can be used as teaching materials to improve students’ understanding of the relationship between language, society, and culture represented in literary works.